Is sleep bruxism associated with smartphone use, neck pain, and sleep features among adolescents? - Ivana Meyer PRADO; Letícia Fernanda MOREIRA-SANTOS; Gabriela de Faria e Barboza HOFFMAM; Lucas Guimarães ABREU; Sheyla Márcia AUAD; Isabela Almeida PORDEUS; Júnia Maria SERRA-NEGRA (Brazilian Oral Research)
Abstract An association between bruxism and musculoskeletal disorders, such as neck pain, has been established. This study investigated the association of possible sleep bruxism (PSB) activities, including grinding, bracing, and thrusting, with smartphone use, smartphone-induced neck pain, and sleep features. This cross-sectional study involved 403 Brazilian adolescents aged 11 to 19 years. A self-administered questionnaire was used to assess the severity of PSB, smartphone use, smartphone-induced neck pain, and sleep features (sleep duration and quality and history of nightmares). Sociodemographic factors, as well as snoring and drooling on the pillow, were considered potential confounders and were assessed based on reports from parents/caregivers. Participants were selected using multiple-stage sampling. Descriptive analysis and multinomial regression were performed (p ≤ 0.05). Adolescents reporting nightmares at least once a month (OR = 3.402; 95%CI: 1.315–8.802) and sometimes experiencing smartphone-induced neck pain (OR: 3.697, 95%CI: 1.103–12.388) were more likely to report moderate/severe grinding. Drooling on the pillow (OR = 3.105, 95%CI: 1.316–7.329), poor/fairly good sleep quality (OR = 2.717, 95%CI: 1.279–5.770), and smartphone-induced neck pain (OR = 3.227, 95%CI: 1.121–9.285) were associated with mild bracing. Adolescents experiencing nightmares once a week (OR = 3.209, 95% CI: 1.202– 8.565) had a higher prevalence of mild thrusting. Self-reported smartphone-induced neck pain, nightmares, poor/fairly good sleep quality, and drooling on the pillow were associated with a higher prevalence of PSB activities among Brazilian adolescents. Clinicians and researchers are encouraged to include assessments of smartphone use and sleep features in anamnesis, promoting a comprehensive approach to PSB, from diagnosis to treatment.